Analysis of the model of interrelation between the geometry of thermoelement branches and reliability indicators of the cascade cooler - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
We examined influence of the geometry of thermoelement branches and the distribution of thermoelements in cascades of the two-cascade thermoelectric cooling devices on the reliability indicators. An analysis was conducted for the operating range of temperature difference, nominal thermal load under the mode of maximum refrigeration capacity at preset current. A mathematical model was constructed, connecting reliability indicators of the cooler and the geometry of thermoelement branches, distribution of thermoelements in the cascades, temperature differential and operating current in the cascades, and thermal load. We ran an analysis of the model, which showed that the failure rates and the probabilities of failure-free operation demonstrate clearly pronounced extrema that can be applied when designing the two-cascade thermoelectric cooling devices with enhanced reliability. The analysis of the obtained model revealed that the variation of the geometry of thermoelements and their distribution in the cascades could be employed to achieve a two-time reduction in the failure rate of a thermoelectric cooler and a corresponding increase in the probability of failure-free operation.